2018
DOI: 10.1002/dneu.22628
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Development of the Posterior Hypothalamic Theta Rhythm and Local Cell Discharges in Rat Brain Slices

Abstract: Theta rhythms have been recorded from rat brain slices of the posterior hypothalamic area (PHa), including the supramammillary and posterior hypothalamic nuclei. Additionally, in numerous studies theta-related neurons were identified in the PHa according to the classification of Bland and Colom (Progress in Neurobiology, 41, 157-208, 1993). It is currently widely accepted that the PHa contributes to the process of HPC theta frequency programming at least in certain behavioral states. The postnatal development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 55 publications
(191 reference statements)
2
9
0
Order By: Relevance
“…On the other hand, the only type of theta‐related neurons extracellularly recorded in posterior hypothalamic slice preparations were theta‐on phasic cells. Interestingly, a similar uneven distribution of given theta‐related subtypes of neurons was observed in previous studies concerning the cellular correlates of PHa neuronal firing in relation to local cholinergic theta field oscillations (Bocian et al, 2016; Caban et al, 2018). The very low probability of recording theta‐on phasic neurons in the PHa of urethane‐anesthetized animals may seem surprising considering that a relatively large number of these cells was found in this area in some of the previous in vivo studies.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…On the other hand, the only type of theta‐related neurons extracellularly recorded in posterior hypothalamic slice preparations were theta‐on phasic cells. Interestingly, a similar uneven distribution of given theta‐related subtypes of neurons was observed in previous studies concerning the cellular correlates of PHa neuronal firing in relation to local cholinergic theta field oscillations (Bocian et al, 2016; Caban et al, 2018). The very low probability of recording theta‐on phasic neurons in the PHa of urethane‐anesthetized animals may seem surprising considering that a relatively large number of these cells was found in this area in some of the previous in vivo studies.…”
Section: Discussionsupporting
confidence: 81%
“…Until recently, it seemed that the only structure containing theta‐related cells within its neuronal networks and having the ability to generate local theta field potentials was the hippocampal formation (Bland & Colom, 1993; Colom & Bland, 1987; Konopacki et al, 2006; Kowalczyk et al, 2013; Smythe et al, 1991). However, studies performed during the past few years have revealed that the PHa can also be recognized as an independent theta generator in which neurons correlated with local oscillatory activity are present (Bocian et al, 2016; Caban et al, 2018). The ability of the SuM and posterior hypothalamic nuclei to generate local theta field potentials and accompanying cell discharges independently of other brain structures was discussed earlier in detail.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations